2012
DOI: 10.1089/sur.2011.004
|View full text |Cite
|
Sign up to set email alerts
|

Breast Implant Infections after Surgical Reconstruction in Patients with Breast Cancer: Assessment of Risk Factors and Pathogens over Extended Post-Operative Observation

Abstract: Extended post-operative surveillance is indicated, at least for the first six months after breast implant placement, particularly for women who need radiotherapy or chemotherapy after implant surgery. Gram-negative bacilli may be involved more often in late infections than otherwise expected. This finding may influence initial empiric antibiotic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 21 publications
1
22
1
Order By: Relevance
“…A higher proportion (42-44%) of Gram-negative bacilli has been reported recently in breast implant infection after surgical reconstruction in patients with breast cancer. 10,22 No significant difference in Gram-negative bacilli between breast implant infections after surgical reconstruction in patients with breast cancer compared with breast implant infections after aesthetic breast augmentation were found (3/14 vs. 7/23, p = 0.7099). It was found that Gram-negative bacilli breast implant infections were not significantly involved in late infections compared to acute infections (7/21 vs. 3/16, p = 0.4613).…”
Section: Discussionmentioning
confidence: 94%
“…A higher proportion (42-44%) of Gram-negative bacilli has been reported recently in breast implant infection after surgical reconstruction in patients with breast cancer. 10,22 No significant difference in Gram-negative bacilli between breast implant infections after surgical reconstruction in patients with breast cancer compared with breast implant infections after aesthetic breast augmentation were found (3/14 vs. 7/23, p = 0.7099). It was found that Gram-negative bacilli breast implant infections were not significantly involved in late infections compared to acute infections (7/21 vs. 3/16, p = 0.4613).…”
Section: Discussionmentioning
confidence: 94%
“…For this reason we decided to evaluate patients according to a graded definition of infection derived and adapted from infections in neutropenic patients [24]. Post-operative implant infections types [2] were defined as possible (fever, minimal local edema, and inflammation resolving on empiric antibiotic therapy), probable (cellulitis, leukocytosis, systemic inflammation, echographic evidence of inflammation, or peri-prosthetic liquid accumulation, without microorganism isolation on echographic needle aspiration or blood culture), and proved (criteria for probable infection with cellulitis and presence of purulent discharge and microorganism isolation). Implant infections were further defined according to the time lapse after implantation as ''early'' when occurring within 60 d from surgery (DFS) and ''late'' when occurring >60 DFS.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, not all reconstructive breast implant infections, in cancer patients, occur early after surgery (i.e., <60 d) [2,15]. Late breast implant infection occurring months to years after surgery still represents a grey area of our understanding with particular regard to incidence, etiology, physiopathology, and management, and are sometimes considered rare chance events in everyday clinical practice.…”
mentioning
confidence: 99%
“…The risk of infection is much higher (up to 10 times) in patients undergoing reconstructive surgery as compared to in those undergoing aesthetic surgery because the former group of patients have a higher incidence of underlying (systemic and local) comorbidities, prior chemotherapy and radiotherapy, and a greater degree of local tissue trauma. 22,89 The use of human acellular dermal matrix for cosmetic breast augmentation is associated with a higher risk of infection (relative risk 2.47) and other complications as compared to conventional submuscular reconstructions. 28 The routes of infection for breast implants are similar to those for other implants such as joint prostheses and heart valves.…”
Section: Breast Augmentation Proceduresmentioning
confidence: 99%